Air Force One [videorecording (DVD)] - Ford, Harrison, 1942-; Oldman, Gary; Close, Glenn, 1947-; Crewson, Wendy; Petersen, Wolfgang (Director's signature series., 1998)
An uncompromising U.S. President has just told the world he will not negotiate with terrorists. But when Russian terrorists hijack Air Force One, the world's most secure and extraordinary aircraft, the President is faced with a nearly impossible decision-- give in to terrorist demands or sacrifice not only the country's dignity, but the lives of his wife and daughter.